Optical sheet adhesive

By using a combination of a resin with a high glass transition temperature and a multifunctional epoxy resin in the adhesive, combined with a cationic polymerization initiator, the problem of insufficient transparency and shape retention of the adhesive in the prior art is solved, and the problem of achieving the problem of insufficient transparency and shape retention of the adhesive in the prior art is realized. A sheet-like adhesive for optical use with high transparency and high bending properties.

CN115279854BActive Publication Date: 2024-12-13LINTEC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180025851.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-03-26
Publication Date
2024-12-13
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

When the conventional adhesive containing epoxy resin improves the toughness and bending properties of the cured product, it is easy to reduce transparency, and it is difficult to maintain the shape before curing, and it is difficult to meet the requirements of the sheet-like adhesive for optical use.

Method used

The combination of adhesive resin containing a glass transition temperature of 50°C or above and a multifunctional epoxy resin is adjusted to improve the transparency and shape retention of the cured substance, and at the same time, the curing is improved by cationic polymerization initiator. Efficiency and stability of the reaction.

Benefits of technology

It is achieved to provide cured substances with excellent transparency and high bending properties under low temperature conditions, and maintain the shape before curing, which is suitable for the manufacturing of optically related equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 400280DEST_PATH_IMAGE002
    Figure 400280DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The optical sheet adhesive comprises the following components (A) and (B), and provides a storage shear modulus (G') at 0°C. 0 ) is 2×10 7 Pa or less. The optical sheet adhesive provides a cured product having excellent transparency and bendability, and a small difference between the bendability under low temperature conditions and the bendability under high temperature conditions. (A) component: an adhesive resin component containing an adhesive resin having a glass transition temperature (Tg) of 50°C or more; (B) component: an epoxy-based curing component containing a multifunctional epoxy resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to providing a cured product having excellent transparency and high bendability under low temperature conditions, and further an optical sheet-like adhesive having excellent shape retention before curing. Background Art

[0002] In recent years, various devices such as display devices and light-emitting devices have been made more flexible in order to improve portability, installation, design, and visual recognition. Therefore, it is desirable to provide a highly bendable cured adhesive for use in the manufacture of flexible devices.

[0003] Conventionally, when manufacturing devices, sheet-shaped adhesives containing epoxy resins are sometimes used. However, cured products of adhesives containing epoxy resins tend to have high storage elastic modulus and poor toughness.

[0004] For example, Patent Document 1 describes a thermosetting adhesive sheet comprising an epoxy resin, wherein the cured product of the thermosetting adhesive sheet has a storage elastic modulus (x1) of 1 GPa or more at 25°C and a storage elastic modulus (x2) of 1 GPa or more at 100°C.

[0005] As a method for improving the toughness of a cured product of a resin composition containing an epoxy resin, a method of adding rubber fine particles or the like to the resin composition is known.

[0006] For example, Patent Document 2 describes an epoxy resin composition containing a bisphenol E epoxy resin, rubber particles, and a curing agent. Patent Document 2 also describes that the cured product of the epoxy resin composition has excellent toughness.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-110128

[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-87124. Summary of the invention

[0011] Problems to be solved by the invention

[0012] As described in Patent Document 2, by adding rubber particles to a resin composition containing an epoxy resin, the toughness and impact resistance of the cured product can sometimes be improved. However, the cured product of the resin composition containing rubber particles tends to have poor transparency. Therefore, a sheet-like adhesive containing an excessive amount of rubber particles has a risk of being unsuitable as an optical sheet-like adhesive.

[0013] Furthermore, according to the research conducted by the present inventors, even if there is a possibility of providing a sheet-like adhesive having excellent transparency and a cured product with high flexibility under low temperature conditions, it is sometimes difficult to ensure the cohesiveness of the sheet-like adhesive before curing and to obtain a sheet-like adhesive having excellent shape retention before curing.

[0014] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide an optical sheet-like adhesive which provides a cured product having excellent transparency and high bendability under low temperature conditions and excellent shape retention before curing.

[0015] Means for solving problems

[0016] The present inventors have conducted intensive research on a sheet-like adhesive containing an adhesive resin and an epoxy resin to solve the above problems, and have completed the present invention. According to the present invention, the following optical sheet-like adhesives [1] to [8] are provided.

[0017] [1] An optical sheet adhesive comprising the following components (A) and (B), wherein a cured product of the optical sheet adhesive has a storage shear modulus (G′) at 0° C. 0 ) is 2×10 7 Below Pa,

[0018] (A) Component: Adhesive resin component containing an adhesive resin having a glass transition temperature (Tg) of 50° C. or higher

[0019] (B) Component: an epoxy-based curable component containing a multifunctional epoxy resin.

[0020] [2] The optical sheet-like adhesive according to [1], wherein at least one of the resins having a glass transition temperature (Tg) of 50° C. or higher constituting the component (A) is a phenoxy resin.

[0021] [3] The optical sheet-like adhesive according to [1] or [2], wherein at least one of the resins having a glass transition temperature (Tg) of 50° C. or higher constituting the component (A) is a polyvinyl acetal resin.

[0022] [4] The optical sheet adhesive according to any one of [1] to [3], wherein at least one of the multifunctional epoxy resins constituting the component (B) is a resin [epoxy resin (BL)] that provides a cured product having a glass transition temperature (Tg) of 25° C. or less.

[0023] [5] The optical sheet adhesive according to [4], wherein the content of the epoxy resin (BL) is 50 to 75% by mass based on the entire optical sheet adhesive.

[0024] [6] The optical sheet-like adhesive according to [4] or [5], wherein the epoxy resin (BL) is a polyfunctional epoxy resin having an oxyalkylene structure.

[0025] [7] The optical sheet adhesive according to any one of [1] to [6], wherein at least one of the multifunctional epoxy resins constituting the component (B) is a liquid resin at 23°C.

[0026] [8] The optical sheet adhesive according to any one of [1] to [7], wherein the haze of a cured product of the optical sheet adhesive is 1% or less.

[0027] Effects of the Invention

[0028] According to the present invention, there is provided an optical sheet-like adhesive which provides a cured product having excellent transparency and high bendability under low temperature conditions and which has excellent shape retainability before curing. DETAILED DESCRIPTION

[0029] The optical sheet-like adhesive of the present invention contains the above-mentioned components (A) and (B), and satisfies the storage shear modulus requirement at 0° C. of the above-mentioned cured product (hereinafter also referred to as “low-temperature modulus requirement”).

[0030] The sheet-like adhesive refers to an adhesive formed into a sheet that shows no fluidity at room temperature (23° C., the same applies hereinafter). In the present invention, the sheet-like adhesive may be in a short strip shape or a long strip shape (tape shape).

[0031] In this specification, "optical sheet-like adhesive" may be described as "sheet-like adhesive".

[0032] [(A) ingredient]

[0033] The optical sheet-like adhesive of the present invention contains, as component (A), an adhesive resin component including an adhesive resin having a glass transition temperature (Tg) of 50° C. or higher (hereinafter sometimes referred to as “adhesive resin (AH)”).

[0034] In the present invention, the “adhesive resin component” refers to a single adhesive resin when the optical sheet-like adhesive contains one adhesive resin, and refers to a mixture of two or more adhesive resins when the optical sheet-like adhesive contains two or more adhesive resins.

[0035] The "adhesive resin" refers to a polymer component that imparts shape retention or flexibility to a sheet-like adhesive.

[0036] Adhesives containing multifunctional epoxy resins, such as the optical sheet adhesive of the present invention, have the risk of not being able to maintain a certain shape in an uncured state. In particular, in the optical sheet adhesive of the present invention, as the content ratio of the component (B) increases, the curing of the optical sheet adhesive can be more significantly induced (i.e., a cured product with higher hardness is obtained), but as the content ratio of the component (B) increases, the shape retention of the optical sheet adhesive is further reduced.

[0037] In order to solve this problem, the present invention utilizes the component (A). That is, the optical sheet-like adhesive of the present invention contains the component (A), and thus has sufficient shape retention even when a large amount of the component (B) is contained.

[0038] The component (A) consists only of a binder resin, and contains at least a binder resin (AH) as an essential component.

[0039] The component (A) may consist of the binder resin (AH) alone, or may contain a binder resin having a glass transition temperature (Tg) lower than 50° C. in addition to the binder resin (AH). Preferably, the component consists of the binder resin (AH) alone.

[0040] The adhesive resin (AH) is not particularly limited as long as it is a polymer component having a glass transition temperature (Tg) of 50° C. or higher and imparting shape retention or flexibility to the optical sheet-like adhesive.

[0041] The glass transition temperature (Tg) of the binder resin (AH) is 50° C. or higher, preferably 80° C. or higher. The upper limit is not particularly limited, but is usually 200° C. or lower.

[0042] The glass transition temperature (Tg) of the binder resin (AH) can be measured in accordance with JISK7121 using a differential scanning calorimeter.

[0043] When the component (A) does not contain the adhesive resin (AH), the shape retention of the optical sheet adhesive is insufficient, so that, for example, when the release sheet is peeled off in order to use the optical sheet adhesive, there is a risk of the optical sheet adhesive being broken. That is, the optical sheet adhesive that does not contain the adhesive resin (AH) has poor shape retention before curing.

[0044] From such a viewpoint, the content of the adhesive resin (AH) is preferably 20 to 45% by mass, more preferably 25 to 43% by mass, based on the entire optical sheet-like adhesive.

[0045] The weight average molecular weight (Mw) of the binder resin (AH) is preferably 10,000 to 300,000, more preferably 30,000 to 200,000.

[0046] The weight average molecular weight (Mw) of the binder resin (AH) can be determined as a standard polystyrene-equivalent value by performing gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.

[0047] Examples of the binder resin (AH) include olefin resins, acrylic polymers, polyester resins, polyvinyl alcohol resins, polyvinyl acetal resins, polyvinyl chloride, phenoxy resins, polyamide resins, cellulose materials, polyvinyl ethers, polyimide resins, styrene-isoprene-styrene block copolymers, and styrene-butadiene-styrene block copolymers.

[0048] The binder resin (AH) may be used alone or in combination of two or more.

[0049] At least one kind of the binder resin (AH) is preferably a phenoxy resin.

[0050] Phenoxy resin is a polymer having a main chain of an addition polymerization structure of an aromatic diol and an aromatic diglycidyl ether. Phenoxy resin generally belongs to a high molecular weight epoxy resin and refers to a resin having a polymerization degree of about 100 or more.

[0051] Some phenoxy resins have a high glass transition temperature (Tg), and such phenoxy resins are suitable for use as the binder resin (AH).

[0052] The epoxy equivalent of the phenoxy resin is preferably 5,000 g / eq or more, more preferably 7,000 g / eq or more. The value of the epoxy equivalent can be measured in accordance with JIS K7236 (hereinafter the same).

[0053] Examples of the phenoxy resin include bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol S type phenoxy resin, bisphenol A type and bisphenol F type copolymer type phenoxy resin, bisphenol E type phenoxy resin, naphthalene type phenoxy resin, novolac type phenoxy resin, biphenyl type phenoxy resin, and cyclopentadiene type phenoxy resin.

[0054] These phenoxy resins can be used alone or in combination of two or more.

[0055] The phenoxy resin can be obtained by a method of reacting a bifunctional phenol with an epihalohydrin to obtain a high molecular weight, or by a method of subjecting a bifunctional epoxy resin to a polyaddition reaction with a bifunctional phenol.

[0056] For example, the phenoxy resin can be obtained by reacting a difunctional phenol with an epihalohydrin in the presence of an alkali metal hydroxide in an inert solvent at a temperature of 40 to 120° C. Alternatively, the phenoxy resin can be obtained by reacting a difunctional epoxy resin with a difunctional phenol in the presence of a catalyst such as an alkali metal compound, an organic phosphorus compound, a cyclic amine compound, in an organic solvent such as an amide solvent, an ether solvent, a ketone solvent, a lactone solvent, an alcohol solvent, etc. having a boiling point of 120° C. or higher, at a reaction solid content concentration of 50% by weight or less, and heating to 50 to 200° C.

[0057] The difunctional phenols are not particularly limited as long as they are compounds having two phenolic hydroxyl groups. For example, monocyclic difunctional phenols such as hydroquinone, 2-bromohydroquinone, resorcinol, and catechol; bisphenols such as bisphenol A, bisphenol F, bisphenol AD, and bisphenol S; dihydroxybiphenyls such as 4,4'-dihydroxybiphenyl; dihydroxyphenyl ethers such as bis(4-hydroxyphenyl)ether; and those having linear alkyl groups, branched alkyl groups, aryl groups, hydroxymethyl groups, allyl groups, cyclic aliphatic groups, halogens (tetrabromobisphenol A, etc.), nitro groups, etc. introduced into the aromatic rings of these phenol skeletons; and polycyclic difunctional phenols having linear alkyl groups, branched alkyl groups, allyl groups, substituted allyl groups, cyclic aliphatic groups, alkoxycarbonyl groups, etc. introduced into the carbon atoms located in the center of these bisphenol skeletons.

[0058] Examples of the epihalohydrin include epichlorohydrin, epibromohydrin, and epiiodohydrin.

[0059] In the present invention, commercially available phenoxy resins may be used, for example, YX7200 (glass transition temperature (Tg): 150°C), YX6954 (phenoxy resin containing a bisphenol acetophenone skeleton, glass transition temperature (Tg): 130°C) manufactured by Mitsubishi Chemical Corporation, and YP70 (glass transition temperature (Tg): 70°C) manufactured by Nippon Steel Chemicals & Materials Corporation.

[0060] At least one type of binder resin (AH) is preferably a polyvinyl acetal resin.

[0061] The polyvinyl acetal resin is a polymer obtained by an acetalization reaction between a hydroxyl group of polyvinyl alcohol (or a partially saponified product of an ester thereof; the same shall apply hereinafter) and an aldehyde.

[0062] In order to obtain a photocurable sheet adhesive that provides a cured product with better bonding strength, the optical sheet adhesive preferably contains a large amount of component (B). However, the optical sheet adhesive containing a large amount of component (B) tends to have a reduced uniformity of the components, and as a result, there is a risk that the transparency of the obtained cured product is reduced.

[0063] By using a polyvinyl acetal resin as the adhesive resin (AH), the uniformity of the components can be improved. Therefore, by using a polyvinyl acetal resin, an optical sheet-like adhesive that provides a cured product with excellent coating suitability can be easily obtained.

[0064] When a phenoxy resin is used as the adhesive resin (AH), the uniformity of such components may be reduced. However, when the component (A) contains both a phenoxy resin and a polyvinyl acetal resin, the uniformity of the components of the adhesive for an optical sheet can be improved.

[0065] Examples of the polyvinyl acetal resin include polyvinyl butyral obtained by reacting polyvinyl alcohol with butyraldehyde, polyvinyl formal obtained by reacting polyvinyl alcohol with formaldehyde, and polyvinyl acetal obtained by reacting polyvinyl alcohol with acetaldehyde.

[0066] These polyvinyl acetal resins may be used alone or in combination of two or more.

[0067] The polyvinyl acetal resin can be synthesized by reacting polyvinyl alcohol with aldehyde using an acid catalyst in an appropriate solvent. Examples of the solvent used include water; alcohol solvents such as methanol and ethanol; mixed solvents containing water and alcohol; and aprotic polar solvents such as dimethyl sulfoxide.

[0068] Furthermore, the polyvinyl acetal-based resin can also be synthesized by adding an acid catalyst and an aldehyde to a polyvinyl acetate solution to allow the mixture to react.

[0069] The acid catalyst used is not particularly limited, and examples thereof include organic acids such as acetic acid and p-toluenesulfonic acid; and inorganic acids such as nitric acid, sulfuric acid, and hydrochloric acid.

[0070] The above reaction is stopped by adding a base. The base used is not particularly limited, and examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide; ammonia; metal nitrates such as sodium nitrate; metal carbonates such as sodium carbonate and potassium carbonate; and metal bicarbonates such as sodium bicarbonate and potassium bicarbonate.

[0071] [(B) ingredient]

[0072] The optical sheet-like adhesive of the present invention contains an epoxy-based curable component containing a polyfunctional epoxy resin (hereinafter sometimes referred to as “epoxy resin (BP)”) as the component (B).

[0073] In the present invention, the “epoxy-based curable component” refers to a single epoxy resin when the optical sheet-like adhesive contains one epoxy resin, and refers to a mixture of two or more epoxy resins when the optical sheet-like adhesive contains two or more epoxy resins.

[0074] The "polyfunctional epoxy resin" refers to an epoxy resin having two or more epoxy groups in the molecule.

[0075] In addition, even if it is a compound having an epoxy group, the substance belonging to the adhesive resin which comprises the (A) component does not comprise the (B) component.

[0076] The optical sheet adhesive containing the component (B) has curability, and the cured product of the optical sheet adhesive has a certain degree of hardness even under high temperature conditions (eg, 100° C.).

[0077] The content of the component (B) is preferably 50 to 75% by mass, more preferably 52 to 70% by mass, and even more preferably 54 to 65% by mass based on the entire optical sheet-like adhesive.

[0078] When the content of component (B) is within the above range, it is easy to obtain an optical sheet adhesive having a certain degree of hardness even under high temperature conditions. Furthermore, the shape retention and adhesion of the optical sheet adhesive and the shape retention of the cured product under high temperature conditions are well balanced.

[0079] The component (B) consists only of epoxy resin, and contains at least epoxy resin (BP) as an essential component.

[0080] The component (B) may consist of the epoxy resin (BP) alone, or may contain a monofunctional epoxy resin in addition to the epoxy resin (BP), but preferably consists of the epoxy resin (BP) alone.

[0081] The content of the epoxy resin (BP) constituting the component (B) (when two or more epoxy resins (BP) are present, the total amount thereof) is usually 90 to 100% by mass, preferably 95 to 100% by mass, based on the total amount of the component (B).

[0082] When the content of the epoxy resin (BP) is 90% by mass or more based on the total amount of the component (B), an optical sheet-like adhesive having a certain degree of hardness even under high temperature conditions can be easily obtained as a cured product.

[0083] The weight average molecular weight (Mw) of the epoxy resin (BP) is preferably 100 to 5,000, more preferably 200 to 4,000.

[0084] The weight average molecular weight (Mw) of the epoxy resin (BP) can be determined as a standard polystyrene-equivalent value by performing gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.

[0085] The epoxy equivalent of the epoxy resin (BP) is preferably 100 g / eq to 500 g / eq, more preferably 115 g / eq to 450 g / eq. By curing an optical sheet adhesive containing an epoxy resin (B) having an epoxy equivalent of 100 g / eq to 500 g / eq, a cured product having excellent bonding strength can be obtained.

[0086] Examples of the epoxy resin (BP) include aliphatic epoxy compounds (excluding alicyclic epoxy compounds), aromatic epoxy compounds, and alicyclic epoxy compounds.

[0087] Examples of the aliphatic epoxy compound include 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol tetraglycidyl ether, dipentaerythritol hexaglycidyl ether, polyethylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether.

[0088] Examples of the aromatic epoxy compound include glycidyl ethers of bisphenol A, bisphenol F, or compounds obtained by further adding alkylene oxide thereto, epoxy novolac resins; polyglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups, such as resorcinol, hydroquinone, and catechol; glycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups, such as phenyl dimethanol, phenyl diethanol, and phenyl dibutyl alcohol; glycidyl esters of polyacid aromatic compounds having two or more carboxylic acids, such as phthalic acid, terephthalic acid, and trimellitic acid, etc.

[0089] Examples of the alicyclic epoxy compound include polyglycidyl ethers of polyols having at least one alicyclic structure, such as dicyclopentadienyl dimethanol diglycidyl ether and hydrogenated products of bisphenol A, and cycloolefin oxide compounds such as cyclohexene oxide and cyclopentene oxide-containing compounds obtained by epoxidizing a cyclohexene or cyclopentene ring-containing compound with an oxidizing agent.

[0090] These epoxy resins (BP) can be used alone or in combination of two or more.

[0091] At least one of the epoxy resins (BP) is preferably a resin that provides a cured product having a glass transition temperature (Tg) of 25°C or less (hereinafter sometimes referred to as "epoxy resin (BL)"; that is, the epoxy resin (BL) is a resin that provides a cured product having a glass transition temperature (Tg) of 25°C or less when fully cured alone or in the presence of a curing agent or the like). The epoxy resin (BL) is preferably a resin that provides a cured product having a glass transition temperature (Tg) of -5°C or less, and more preferably a resin that provides a cured product having a glass transition temperature (Tg) of -20°C or less.

[0092] By using the component (B) containing the epoxy resin (BL), it is easy to obtain an optical sheet adhesive that provides a cured product having a low storage shear modulus (G') even under low temperature conditions. Therefore, the optical sheet adhesive containing the epoxy resin (BL) easily satisfies the above-mentioned low-temperature elastic modulus requirement. Therefore, it is easy to obtain an optical sheet adhesive having better bendability under low temperature conditions (e.g., 0°C).

[0093] When the optical sheet adhesive of the present invention contains the epoxy resin (BL), the content of the epoxy resin (BL) is preferably 50 to 75% by mass, more preferably 52 to 70% by mass, and even more preferably 54 to 65% by mass based on the entire optical sheet adhesive.

[0094] When the content of the epoxy resin (BL) is 50% by mass or more based on the entire optical sheet-like adhesive, it is easy to obtain an optical sheet-like adhesive that satisfies the above-mentioned low-temperature elastic modulus requirements.

[0095] The glass transition temperature (Tg) of the cured product of epoxy resin (BP) can be determined by differential scanning calorimetry using a sample obtained by a curing reaction under conditions in which epoxy resin (BP) is fully cured. The conditions for preparing the sample (curing conditions of epoxy resin (BP)) include, for example, the conditions described in the Examples.

[0096] Examples of the epoxy resin (BL) include polyfunctional epoxy resins having an oxyalkylene structure. Polyfunctional epoxy resins having an oxyalkylene structure tend to provide cured products having relatively low glass transition temperatures (Tg), and are therefore preferably used as the epoxy resin (BL).

[0097] Examples of the oxyalkylene structure include oxymethylene, oxyethylene, oxypropylene, oxytrimethylene, oxybutylene, oxypentylene, oxyhexylene, oxyheptylene, oxyoctylene, oxynonylene, oxydecylene, oxyundecylene, oxydodecylene, oxytridecylene, oxytetradecylene, oxypentadecylene, oxycyclopropylene, oxycyclobutylene, oxycyclopentylene, oxycyclohexylene, oxydecahydronaphthylene, oxynorbornenylidene, and oxyadamantylene.

[0098] It is preferred that at least one of the epoxy resins (BP) is in a liquid state at 23°C.

[0099] “Liquid at 23° C.” means having fluidity at 23° C. The epoxy resin (BP) preferably has a viscosity of 2 to 10,000 mPa·s as measured at 23° C. and 1.0 rpm using an E-type viscometer.

[0100] By using an epoxy resin (BP) that is liquid at 23° C., an optical sheet adhesive having a low elastic modulus at room temperature can be obtained. Such an optical sheet adhesive has excellent adhesion at room temperature, so it is not necessary to heat and soften the optical sheet adhesive in the bonding step.

[0101] When the optical sheet adhesive of the present invention contains an epoxy resin (BP) that is liquid at 23°C, the content of the epoxy resin (BP) that is liquid at 23°C is preferably 50 to 75% by mass, more preferably 52 to 70% by mass, and even more preferably 54 to 65% by mass based on the entire optical sheet adhesive.

[0102] When the content of the epoxy resin (B) which is liquid at 23° C. is within the above range, an optical sheet-like adhesive having the above characteristics can be easily obtained.

[0103] The epoxy resin (BL) is preferably liquid at 23° C. from the viewpoint of easily obtaining an optical sheet adhesive that provides a cured product having a low storage shear modulus (G′) even under low temperature conditions and improving the adhesiveness of the optical sheet adhesive.

[0104] [(C) ingredient]

[0105] The optical sheet-like adhesive of the present invention may contain a cationic polymerization initiator as the component (C).

[0106] The cationic polymerization initiator is preferred because it allows the polymerization reaction of the component (B) to proceed efficiently and can improve the storage stability of the optical sheet-like adhesive compared to other curing agents.

[0107] Examples of the cationic polymerization initiator include thermal cationic polymerization initiators and photocationic polymerization initiators. From the viewpoint of improving the storage stability of the adhesive and allowing the polymerization reaction to proceed rapidly after irradiation with light, photocationic polymerization initiators are preferred.

[0108] The photocationic polymerization initiator is a compound that generates cationic species by irradiation with ultraviolet rays to initiate a curing reaction of a cation curable compound, and includes a cationic portion that absorbs ultraviolet rays and an anionic portion that is a source of acid.

[0109] Examples of the photocationic polymerization initiator include sulfonium salt compounds, iodonium salt compounds, phosphonium salt compounds, ammonium salt compounds, diazonium salt compounds, selenium salt compounds, oxonium salt compounds, and bromine salt compounds. Among these, sulfonium salt compounds are preferred from the viewpoint of excellent compatibility with other components, and aromatic sulfonium salt compounds having an aromatic group are more preferred.

[0110] Examples of the sulfonium salt compounds include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4'-bis[diphenylsulfonium]diphenyl sulfide-bishexafluorophosphate, 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonium]diphenyl sulfide-bishexafluoroantimonate, 7-[di(p-toluoyl)sulfonium]-2-isopropylthioxanthone hexafluorophosphate, 7-[di(p-toluoyl)sulfonium]-2-isopropylthioxanthone hexafluorophosphate, and 7-[di(p-toluoyl)sulfonium]-2-isopropylthioxanthone hexafluorophosphate. )sulfonium]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluoyl)sulfonium]-2-isopropyltetrakis(pentafluorophenyl)borate, phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-hexafluorophosphate, phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-hexafluoroantimonate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-hexafluorophosphate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonium hexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, 4-{4-(2-chlorobenzoyl)phenylthio}phenylbis(4-fluorophenyl)sulfonium hexafluoroantimonate, halides of thiophenyldiphenylsulfonium hexafluoroantimonate, 4,4',4''-tris(4-fluorophenyl)sulfonium hexafluorophosphate, (β-Hydroxyethoxyphenyl)sulfonium hexafluoroantimonate, 4,4'-bis[diphenylsulfonium]diphenyl sulfide-bishexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium trifluorotris(pentafluoroethyl)phosphate, tris[4-(4-acetylphenylthio)phenyl]sulfonium tris[(trifluoromethyl)sulfonyl]methanide, a salt in which the cation part is 4-(phenylthio)phenyldiphenylsulfonium and the anion part is a phosphorus anion to which fluorine and perfluoroalkyl groups are added, and the like.

[0111] Examples of the iodonium salt compounds include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, di(4-nonylphenyl)iodonium hexafluorophosphate, and (tricumyl)iodonium tetrakis(pentafluorophenyl)borate.

[0112] Examples of the phosphonium salt compound include tri-n-butyl(2,5-dihydroxyphenyl)phosphonium bromide and hexadecyltributylphosphonium chloride.

[0113] Examples of the ammonium salt compound include benzyltrimethylammonium chloride, phenyltributylammonium chloride, and benzyltrimethylammonium bromide.

[0114] The cationic polymerization initiator may be used alone or in combination of two or more.

[0115] When the optical sheet-like adhesive contains a cationic polymerization initiator, the content of the cationic polymerization initiator is preferably 0.1 to 6 parts by mass, more preferably 0.3 to 5 parts by mass, and even more preferably 0.5 to 4 parts by mass based on 100 parts by mass of the component (A).

[0116] The optical sheet adhesive may contain a reactive curing agent other than the cationic polymerization initiator. Examples of the reactive curing agent other than the cationic polymerization initiator include amine compounds such as benzylmethylamine and 2,4,6-trisdimethylaminomethylphenol; imidazole compounds such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-heptadecylimidazole; Lewis acids such as boron trifluoride·monoethylamine complex and boron trifluoride·piperazine complex; and heat-reactive curing agents such as peroxides such as di(tert-butylperoxy)diisopropylbenzene.

[0117] [Other ingredients]

[0118] The optical sheet-like adhesive of the present invention may contain other components within a range not inhibiting the effects of the present invention.

[0119] Examples of other components include additives such as silane coupling agents, ultraviolet absorbers, antistatic agents, light stabilizers, antioxidants, resin stabilizers, fillers, pigments, extenders, and softeners.

[0120] These may be used alone or in combination of two or more.

[0121] When the sheet-like adhesive of the present invention contains these additives, the content thereof can be appropriately determined depending on the purpose.

[0122] [Layer structure of optical sheet adhesive]

[0123] The thickness of the optical sheet-like adhesive of the present invention is usually 1 to 50 μm, preferably 1 to 40 μm, and more preferably 2 to 30 μm.

[0124] The thickness of the optical sheet adhesive can be measured using a known thickness meter according to JIS K 7130 (1999). When the optical sheet adhesive has a release film described below, the thickness of the optical sheet adhesive means the thickness excluding the thickness of the release film.

[0125] The optical sheet-like adhesive of the present invention preferably has a release film on at least one surface, and may have release films on both surfaces, from the viewpoint of protecting the sheet-like adhesive from the external environment.

[0126] It should be noted that the optical sheet adhesive of the present invention having a release film on at least one surface is in a state before use, and the release film is usually peeled off when the optical sheet adhesive of the present invention is used. When the optical sheet adhesive has release films on both surfaces, the release film with the lower release force is usually peeled off first.

[0127] As the release film, a resin film can generally be used.

[0128] Examples of the resin component of the resin film include polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resin, cycloolefin polymer, aromatic polymer, polyurethane polymer, etc. Among these, polyester resin is preferred.

[0129] When the release film has a release agent layer, examples of the release agent include rubber elastomers such as silicone resins, olefin resins, isoprene resins, and butadiene resins, long-chain alkyl resins, alkyd resins, and fluorine resins.

[0130] The thickness of the release film is usually 10 to 300 μm, preferably 10 to 200 μm, and more preferably 15 to 100 μm.

[0131] [Method for producing optical sheet adhesive]

[0132] The method for producing the optical sheet-like adhesive of the present invention is not particularly limited, and for example, it can be produced by a casting method.

[0133] The method of producing an optical sheet-like adhesive by a casting method is to apply an adhesive composition as a raw material on a release film using a known method, and to dry the obtained coating film to obtain an optical sheet-like adhesive with a release film.

[0134] The adhesive composition contains the above-mentioned (A) component and (B) component, and other components as necessary.

[0135] The adhesive composition may further contain a solvent.

[0136] Examples of the solvent include aromatic hydrocarbon solvents such as benzene and toluene; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane; alicyclic hydrocarbon solvents such as cyclopentane, cyclohexane and methylcyclohexane, etc.

[0137] These solvents may be used alone or in combination of two or more.

[0138] When the adhesive composition contains a solvent, the content of the solvent can be appropriately determined in consideration of coating properties and the like.

[0139] The adhesive composition can be prepared by appropriately mixing and stirring the components according to a conventional method.

[0140] The release film used in the production of the optical sheet adhesive functions as a support in the production step of the optical sheet adhesive and also functions as a release film for the optical sheet adhesive in the process until the optical sheet adhesive is used.

[0141] Examples of a method for applying the adhesive composition include spin coating, spray coating, bar coating, knife coating, roll coating, doctor blade coating, die coating, and gravure coating.

[0142] Examples of a method for drying the coating film of the adhesive composition include conventionally known drying methods such as hot air drying, hot roll drying, and infrared irradiation.

[0143] The conditions for drying the coating film are, for example, 80 to 150° C. for 30 seconds to 5 minutes.

[0144] [Characteristics of Optical Sheet Adhesives]

[0145] When the optical sheet-like adhesive of the present invention is photocurable, the optical sheet-like adhesive can be cured by irradiating the optical sheet-like adhesive with ultraviolet rays, for example.

[0146] As a specific example of the ultraviolet light source, there can be mentioned light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, black light fluorescent lamps, metal halide lamps, etc. In addition, as the wavelength of the ultraviolet light irradiated, a wavelength region of 190 to 380 nm can be used.

[0147] The type of ultraviolet rays, the irradiation amount, the irradiation time, etc. can be appropriately determined according to the constituent components of the sheet-like adhesive to be irradiated, the content of each constituent component, and the like.

[0148] The irradiation intensity is preferably 20~1000mW / cm 2 , Light intensity 50~3000mJ / cm 2 about.

[0149] When the optical sheet-like adhesive of the present invention is thermosetting, the conditions for thermosetting the optical sheet-like adhesive are not particularly limited.

[0150] The heating temperature is 80 to 200° C., preferably 90 to 190° C., from the viewpoint of efficiently proceeding the reaction of the component (B).

[0151] The heating time is usually 30 minutes to 12 hours, preferably 1 to 6 hours.

[0152] The optical sheet adhesive of the present invention preferably has a storage shear modulus (G′) of 100° C. of a cured product of the optical sheet adhesive. 100 ) is 1×10 5 Pa or above.

[0153] The optical sheet adhesive that meets such requirements provides a cured product that is difficult to be thermally deformed even under high temperature conditions (e.g., 100° C.), and is therefore suitable for use as an adhesive for devices that require heat resistance. In addition, a cured product that shows a high storage elastic modulus at high temperatures does not soften even at high temperatures, and the adhesiveness is difficult to decrease even if there is a temperature change.

[0154] From this viewpoint, the storage shear modulus (G') of the cured product of the optical sheet adhesive at 100°C is 100 ) is preferably 2×10 5 Pa or more, more preferably 5×10 5 Pa or above.

[0155] The storage shear modulus (G') of the cured product of the optical sheet adhesive at 100°C is 100 ) is not particularly limited, but is 2×10 7 Below Pa.

[0156] Storage shear modulus of the cured product at 100°C (G' 100 ) is 1×10 5 The optical sheet-like adhesive having a viscosity of Pa or more can be efficiently obtained by incorporating a large amount of the component (B) into the optical sheet-like adhesive.

[0157] The optical sheet-like adhesive of the present invention satisfies the above-mentioned low-temperature elastic modulus requirements.

[0158] That is, the storage shear modulus (G') of the cured product of the optical sheet adhesive at 0°C 0 ) is 2×10 7 Below Pa.

[0159] An optical sheet adhesive satisfying the low-temperature elastic modulus requirement provides a cured product having high bendability not only under high-temperature conditions but also under low-temperature conditions (eg, 0° C.), and is therefore suitable as an adhesive for flexible devices.

[0160] From this viewpoint, the storage shear modulus (G') of the cured product of the optical sheet adhesive at 0°C is0 ) is preferably 1.5×10 7 Pa or less, more preferably 1.2×10 7 Below Pa.

[0161] In addition, the storage shear modulus (G') of the cured product of the optical sheet adhesive at 0°C 0 ) is not particularly limited, and as described above, the storage shear modulus (G') at 100°C of the cured product of the optical sheet adhesive of the present invention is 100 ) is preferably 1×10 5 Pa or more. Usually, the storage shear modulus at 0°C will not be lower than the storage shear modulus at 100°C. Therefore, it is preferably 1×10 5 Pa or above.

[0162] An optical sheet-like adhesive that provides a cured product having a low storage shear modulus at low temperatures and that satisfies the low-temperature elastic modulus requirement can be efficiently obtained by incorporating an epoxy resin (BL) into the optical sheet-like adhesive.

[0163] As described above, the cured product of the optical sheet adhesive of the present invention satisfies the low temperature elastic modulus requirement. In addition, the storage shear elastic modulus (G') of the cured product of the optical sheet adhesive at 100°C is 100 ) is preferably 1×10 5 Pa or above.

[0164] In this case, the storage shear modulus (G') of the cured product of the optical sheet-like adhesive of the present invention is usually 1×10 5 ~2×10 7 Pa. The range of the storage shear modulus (G') is narrower than the range of the storage shear modulus (G') of a cured product of a conventional sheet-like adhesive containing an epoxy resin.

[0165] For example, the storage shear modulus (G') of the cured product of the optical sheet adhesive of the present invention at 0°C is 0 ) and storage shear elastic modulus (G') at 100℃ 100 ) ratio (G' 0 / G' 100 ) is usually 1 to 20, preferably 1.2 to 15.

[0166] As described above, the optical sheet adhesive of the present invention is suitable as an adhesive for devices used in an environment with large temperature changes, as long as it provides a cured product with a small change in storage shear modulus (G') in the range of low temperature (near 0°C) to high temperature (near 100°C) (i.e., a cured product with a small difference in bendability between low temperature conditions and high temperature conditions).

[0167] The storage shear modulus (G') of the cured product of the optical sheet-like adhesive can be measured by the method described in Examples.

[0168] The preparation of the measurement sample can be carried out using appropriate curing conditions according to the characteristics of each optical sheet-like adhesive. This also applies to the measurement sample used in measuring the total light transmittance and haze described later.

[0169] For example, when the optical sheet-like adhesive has photocurability, the measurement sample can be prepared under the conditions described in Examples.

[0170] The optical sheet adhesive of the present invention can improve the bendability of the cured product by adjusting the type and amount of the resin contained in the component (A) and the type and amount of the resin contained in the component (B), and does not require a component that reduces transparency. Therefore, the optical sheet adhesive of the present invention has excellent transparency.

[0171] The total light transmittance of the cured product of the optical sheet-like adhesive of the present invention is preferably 90% or more, more preferably 95% or more.

[0172] The total light transmittance of the cured product of the optical sheet-like adhesive can be measured in accordance with JIS K7361-1:1997.

[0173] The haze of the cured product of the optical sheet-like adhesive of the present invention is preferably 1% or less, more preferably 0.5% or less.

[0174] The haze of the cured product of the optical sheet-like adhesive can be measured in accordance with JIS K7136:2000.

[0175] [Applications of optical sheet adhesives]

[0176] As described above, the optical sheet adhesive of the present invention provides a cured product having excellent transparency and high bendability under low temperature conditions, and further excellent shape retention before curing. Therefore, the optical sheet adhesive of the present invention is suitable for use in the manufacture of optical-related devices having light-emitting elements, light-receiving elements, display elements, etc.

[0177] Examples of light-related devices include organic EL displays, organic EL lighting, liquid crystal displays, solar cells, and electronic paper. Example

[0178] The present invention will be described in further detail below with reference to Examples, but the present invention is not limited to the following Examples in any way.

[0179] [Compounds used in Examples or Comparative Examples]

[0180] Binder resin (AH1): phenoxy resin [Mitsubishi Chemical Corporation, trade name: YX7200B35, glass transition temperature (Tg): 150°C, Mw: 30,000]

[0181] · Binder resin (AH2): polyvinyl acetal resin [manufactured by Sekisui Chemical Co., Ltd., trade name: S-LECKS-5Z, glass transition temperature (Tg): 113°C, Mw: 130,000]

[0182] · Binder resin (AH3): polyvinyl acetal resin [manufactured by Sekisui Chemical Co., Ltd., trade name: S-LECBX-25Z, glass transition temperature (Tg): 86°C, degree of polymerization: 2,300]

[0183] · Binder resin (AH4): phenoxy resin [manufactured by Nippon Steel Chemicals & Materials Co., Ltd., trade name: YP70, glass transition temperature (Tg): 70°C, Mw: 55,000]

[0184] Binder resin (A1): phenoxy resin [manufactured by Mitsubishi Chemical Corporation, trade name: YX7180BH40, glass transition temperature (Tg): 15°C, Mw: 40,000]

[0185] · Epoxy resin (BL1): epoxy resin having an oxyalkylene group (liquid at 23°C) [manufactured by Mitsubishi Chemical Corporation, trade name: YX7400, epoxy equivalent: 440 g / eq, glass transition temperature (Tg) of cured product: -69°C]

[0186] · Epoxy resin (BL2): epoxy resin having an oxyalkylene group (liquid at 23°C) [manufactured by ADEKA Corporation, trade name: ED-506, epoxy equivalent: 300 g / eq, glass transition temperature (Tg) of cured product: -50.7°C]

[0187] Epoxy resin (BP1): hydrogenated bisphenol A type epoxy resin (liquid at 23°C) [manufactured by Mitsubishi Chemical Corporation, trade name: YX8000, epoxy equivalent: 205 g / eq, glass transition temperature (Tg) of cured product: 96.4°C]

[0188] · Epoxy resin (BP2): epoxy resin (liquid at 23°C) [manufactured by Daicel, trade name: Celocyside 2021P, epoxy equivalent: 128 to 145 g / eq, glass transition temperature (Tg) of cured product: 94.5°C]

[0189] Cationic polymerization initiator (C1): photocationic polymerization initiator, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate [manufactured by SAN-APRO, trade name: CPI-100P]

[0190] In addition, the glass transition temperature (Tg) of the cured product of the epoxy resin constituting the (B) component is measured by the following method.

[0191] (Preparation of Measurement Samples)

[0192] 0.5 parts by mass of a thermal cationic polymerization initiator [manufactured by Sanshin Chemical Industry Co., Ltd., trade name: SI-B3A] was added to 100 parts by mass of each epoxy resin. The resulting mixture was poured into a polytetrafluoroethylene mold having a thickness of 1 mm and a size of 20 mm×20 mm, and heated at 100° C. for 60 minutes to cure, thereby obtaining a cured product (measurement sample).

[0193] (Differential Scanning Calorimetry)

[0194] Differential scanning calorimetry was performed using a differential scanning calorimeter [manufactured by TA INSTRUMENTS, product name: DSCQ2000] by the following method, and then the glass transition temperature was determined.

[0195] Specifically, the above-mentioned measurement sample was crushed and 5 mg was collected, placed in an aluminum crucible, covered and sealed, temporarily kept at 120°C for 5 minutes, cooled, and then measured at a temperature increase rate of 10°C / min from -100°C to +120°C.

[0196] The temperature of the intersection of a straight line extending from the base line on the low temperature side of the obtained curve to the high temperature side and a tangent line drawn at the point where the slope of the curve in the step-like change portion of the glass transition reaches the maximum is recorded as the glass transition temperature (Tg).

[0197] [Example 1]

[0198] 100 parts by mass of the binder resin (A1) (calculated as the active ingredient excluding the solvent, the same below), 135 parts by mass of the epoxy resin (BL1), and 5.4 parts by mass of the cationic polymerization initiator (C1) were diluted with methyl ethyl ketone to prepare a resin composition (1) having an active ingredient concentration of 40% by mass.

[0199] The resin composition (1) was applied on the release-treated surface of a release film (manufactured by Lintec, trade name: SP-PET752150), and the resulting coating was dried at 100° C. for 2 minutes to form a sheet-like adhesive having a thickness of 5 μm. The release-treated surface of another release film (manufactured by Lintec, trade name: SP-PET381031) was attached to the sheet-like adhesive to prepare a sheet-like adhesive (1) with a release film.

[0200] [Examples 2 to 6, Comparative Examples 1 to 4]

[0201] Sheet-like adhesives (2) to (10) with release films were prepared in the same manner as in Example 1 except that the components listed in Table 1 were used as the components constituting the sheet-like adhesive.

[0202] The following tests were conducted on the release film-attached sheet-like adhesives (1) to (10) obtained in Examples 1 to 6 and Comparative Examples 1 to 4. The results are shown in Table 1.

[0203] [Storage shear modulus of cured product of sheet-like adhesive (G')]

[0204] The storage shear modulus (G′) of the cured product of the sheet-like adhesive was measured by a twisting shear method using a viscoelasticity measuring apparatus (manufactured by Anton Paar, product name: MCR302) in accordance with JIS K7244-6.

[0205] The details of the measurement method are shown below.

[0206] (Preparation of Measurement Samples)

[0207] After peeling off the release sheet from the sheet adhesive with release film obtained in the examples and comparative examples, the sheet adhesive was overlapped to obtain a laminate having a thickness of 0.5 mm. The laminate of the obtained sheet adhesive was irradiated with UV to cure the laminate containing the sheet adhesive. After UV irradiation, the laminate was heated at 100° C. for 60 minutes to promote the curing reaction, thereby obtaining a cured product of the sheet adhesive (laminate).

[0208] It should be noted that UV irradiation was performed using a high-pressure mercury lamp manufactured by EYE GRAPHICS at an illumination of 200 mW / cm 2 , Accumulated light quantity 1000mJ / cm 2 The light meter used was "UVPF-A1" manufactured by EYE GRAPHICS.

[0209] The cured product of the sheet-like adhesive (laminated body) was punched out into a cylindrical body with a diameter of 8 mm (height of 0.5 mm), and this was used as a measurement sample.

[0210] (Determination of storage shear elastic modulus (G'))

[0211] The storage shear modulus (G') was measured using the obtained test sample at a frequency of 1 Hz, a test start temperature of -20°C, a test end temperature of +150°C, and a heating rate of 3°C / min. The values ​​at 0°C and 100°C are shown in Table 1.

[0212] In addition, since the storage shear modulus of the cured products of the sheet-like adhesives (laminated bodies) obtained in Comparative Examples 1 and 2 was too high, slip occurred in the above-mentioned twisting shear method and measurement was impossible.

[0213] Therefore, the storage elastic modulus (E') of the cured products of the sheet-like adhesives (laminated bodies) obtained in Comparative Examples 1 and 2 was measured using a dynamic viscoelasticity measuring apparatus (DMAQ800, manufactured by TA INSTRUMENTS) in accordance with JIS K7244-4 (1999), and the storage shear elastic modulus (G') was calculated from the approximate formula "E'=3G'".

[0214] The details of the method for measuring the storage elastic modulus (E') are shown below.

[0215] (Preparation of Measurement Samples)

[0216] After obtaining a cured product of the sheet-like adhesive (laminated body) by the same method as above, the cured product of the sheet-like adhesive (laminated body) was processed into a size of 30 mm in length and 5 mm in width, and this was used as a measurement sample.

[0217] (Measurement of storage elastic modulus (E'))

[0218] The storage elastic modulus (E') was measured using the obtained measurement sample under the conditions of a frequency of 1 Hz, a test start temperature of -20°C, a test end temperature of 150°C, and a temperature increase rate of 3°C / min.

[0219] (Determination of total light transmittance)

[0220] From the sheet adhesive with a release film obtained in the examples and comparative examples, the release film (light release film, manufactured by Lintec, trade name: SP-PET381130) was peeled off, and the exposed sheet adhesive was attached to glass. After the other release film was peeled off, the sheet adhesive was cured under the same conditions as above to obtain a measurement sample.

[0221] The total light transmittance was measured in accordance with JIS K7361-1:1997 using the measurement sample obtained after background measurement using glass.

[0222] (Determination of haze value)

[0223] From the sheet adhesive with a release film obtained in the examples and comparative examples, the release film (light release film, manufactured by Lintec, trade name: SP-PET381130) was peeled off, and the exposed sheet adhesive was attached to glass. After the other release film was peeled off, the sheet adhesive was cured under the same conditions as above to obtain a measurement sample.

[0224] The haze value was measured in accordance with JIS K7136:2000 using a measurement sample obtained by performing background measurement using glass.

[0225] (Peel test)

[0226] The sheet-like adhesives with release films obtained in Examples and Comparative Examples were processed into a size of 150 mm in length and 50 mm in width to obtain test pieces.

[0227] The obtained test piece was subjected to a 180° peeling test by peeling a peeling film (light peeling film, manufactured by Lintec, trade name: SP-PET381130) at a speed of 300 mm / min. At this time, the case where only the peeled peeling film was peeled off was marked as ○, and the case where the sheet-like adhesive was cleaved and the adhesive adhered to the peeled peeling film was marked as ×. It should be noted that the sheet-like adhesive with a peeling film of Comparative Example 4 failed in this test, and in each of the above measurements, only the portion that was peeled well was used for measurement.

[0228]

[0229] From Table 1, we can know the following.

[0230] The sheet-like adhesives (1) to (6) obtained in Examples 1 to 6 satisfy the low-temperature elastic modulus requirement.

[0231] That is, the storage shear modulus (G') of the cured products of the sheet-like adhesives (1) to (6) at 0°C is 0 ) is 2×10 7 Pa or less. Therefore, the cured products of the sheet adhesives (1) to (6) have high flexibility at low temperatures. In addition, the storage shear modulus (G') of the cured products of the sheet adhesives (1) to (6) at 100°C is 100 ) is high, so the difference between the bending properties under low temperature conditions and the bending properties under high temperature conditions is small.

[0232] Furthermore, the cured products of the sheet-like adhesives (1) to (6) are also excellent in transparency.

[0233] Furthermore, sheet adhesives satisfying the low-temperature elastic modulus requirement tend to have reduced shape retention, but sheet adhesives (1) to (6) contain component (A), so that only the release film can be peeled off intact in the peel test, and have good shape retention.

[0234] On the other hand, since the sheet-like adhesives (7) to (9) obtained in Comparative Examples 1 to 3 did not satisfy the low-temperature elastic modulus requirement, the cured products thereof were inferior in flexural properties at low temperatures.

[0235] The sheet-like adhesive (10) obtained in Comparative Example 4 satisfied the low-temperature elastic modulus requirement and was excellent in bendability. Furthermore, the difference between the bendability under low-temperature conditions and the bendability under high-temperature conditions was small.

[0236] However, since the sheet-like adhesive (10) does not contain the component (A), the peeling film alone cannot be peeled off intact in the peeling test, and the shape retention is poor. In addition, the cured product of the sheet-like adhesive (10) has poor transparency.

Claims

1. An optical sheet adhesive comprising the following components (A) and (B), wherein a cured product of the optical sheet adhesive has a storage shear modulus (G'0) at 0°C of 2×10 7 Below Pa, (A) Component: Adhesive resin component containing an adhesive resin having a glass transition temperature (Tg) of 50° C. or higher Component (B): an epoxy curable component comprising a multifunctional epoxy resin, wherein at least one of the multifunctional epoxy resins is a resin that provides a cured product having a glass transition temperature (Tg) of 25° C. or less [epoxy resin (BL)].

2. The optical sheet-like adhesive according to claim 1, wherein At least one of the resins having a glass transition temperature (Tg) of 50° C. or higher constituting the component (A) is a phenoxy resin.

3. The optical sheet-like adhesive according to claim 1, wherein At least one of the resins having a glass transition temperature (Tg) of 50° C. or higher constituting the component (A) is a polyvinyl acetal resin.

4. The optical sheet-like adhesive according to claim 1, wherein The content of the epoxy resin (BL) is 50 to 75% by mass based on the entire optical sheet-like adhesive.

5. The optical sheet-like adhesive according to claim 1, wherein The epoxy resin (BL) is a multifunctional epoxy resin having an oxyalkylene structure.

6. The optical sheet-like adhesive according to claim 1, wherein At least one of the polyfunctional epoxy resins constituting the component (B) is a liquid resin at 23°C.

7. The optical sheet-like adhesive according to claim 3, wherein The content of the epoxy resin (BL) is 50 to 75% by mass based on the entire optical sheet-like adhesive.

8. The optical sheet-like adhesive according to claim 3, wherein The epoxy resin (BL) is a multifunctional epoxy resin having an oxyalkylene structure.

9. The optical sheet-like adhesive according to claim 3, wherein At least one of the polyfunctional epoxy resins constituting the component (B) is a liquid resin at 23°C.

10. The optical sheet-like adhesive according to claim 1, wherein The haze of the cured product of the optical sheet-like adhesive is 1% or less.

Citation Information

Patent Citations

  • Epoxy resin composition

    JP2013087124A

  • Thermosetting adhesive sheet, article and method for producing article

    JP2017110128A

  • Sheet-like adhesive agent, sealing sheet, electronic device sealed body, and method for manufacturing electronic device sealed body

    CN113646399A